Bahasa Inggris - Cahyani, Cielo Dewi; Mohammad, Asikin (Jurnal Ilmiah Soulmath : Jurnal Edukasi Pendidikan Matematika, 2023)
Numerical skills are important for students to have because numeracy skills are closely applied in everyday life. This article was written with the aim of finding out whether students' numeracy skills can be improved by applying the probing prompting learning model, how are the numeracy skill indicators, and how numeracy skills indicators can be integrated with probing prompting learning. The method used is the Systematic Literature Review (SLR) by reviewing 18 articles of accredited national journals on Sinta 2 to Sinta 5 and international journals indexed by Scopus with the keywords applying the probing prompting model and numeracy skills. The results showed that the implementation of the probing prompting learning model in mathematics learning could improve students' numeracy skills, and indicators of numeracy skills could be integrated in probing prompting learning.